2013
DOI: 10.1371/journal.pone.0060661
|View full text |Cite
|
Sign up to set email alerts
|

Myelosuppressive Conditioning Using Busulfan Enables Bone Marrow Cell Accumulation in the Spinal Cord of a Mouse Model of Amyotrophic Lateral Sclerosis

Abstract: Myeloablative preconditioning using irradiation is the most commonly used technique to generate rodents having chimeric bone marrow, employed for the study of bone marrow-derived cell accumulation in the healthy and diseased central nervous system. However, irradiation has been shown to alter the blood-brain barrier, potentially creating confounding artefacts. To better study the potential of bone marrow-derived cells to function as treatment vehicles for neurodegenerative diseases alternative preconditioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 30 publications
5
28
0
1
Order By: Relevance
“…Previously, we used a non-myeloablative BU regimen to establish sustained chimerism in both wildtype (wt) mice and an ALS model overexpressing mutant human superoxide dismutase 1 (mSOD). We observed engraftment of BMDCs in the spinal cords of both wt and mSOD mice following treatment with 60-100 mg/kg BU and transplantation of GFP + BM cells [11].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previously, we used a non-myeloablative BU regimen to establish sustained chimerism in both wildtype (wt) mice and an ALS model overexpressing mutant human superoxide dismutase 1 (mSOD). We observed engraftment of BMDCs in the spinal cords of both wt and mSOD mice following treatment with 60-100 mg/kg BU and transplantation of GFP + BM cells [11].…”
Section: Introductionmentioning
confidence: 88%
“…However, a limitation to this approach is the requirement for lethal total-body irradiation (TBI) to achieve adequate BM chimerism, a protocol which can affect blood-brain barrier (BBB) permeability [5], as well as the function of endogenous microglia [6,7]. Several recent studies have demonstrated the effectiveness of the milder myelosuppressive conditioning agent busulfan (BU; busulfex) for achieving BM chimerism [8][9][10][11][12], compared to BM conditioning by TBI. We evaluated BU in a murine model of AD to determine if BU was capable of producing BM chimerism, as well as BMDC accumulation in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with irradiated mice, engraftment of GFP + Iba1 + cells was strongly reduced in BU-treated mice both under normal conditions and after facial nerve axotomy. In another study, Lewis et al [95] reported that BU conditioning leads to a weaker infiltration of BMDC in the spinal cord of SOD1 mice in comparison with irradiation. However, the authors observed a significant recruitment of BMDC into the spinal cord of wild-type mice treated with BU under normal conditions.…”
Section: Chemotherapy-based Conditioningmentioning
confidence: 95%
“…Several studies in mouse came out lately comparing the effects of BU-and irradiation-based conditioning regarding microglial engraftment, BBB dysfunction and the neuroinflammatory response [94][95][96][97][98]. Our group compared a fully-myeloablative dose of 10 Gy WBI and a chemotherapeutic regimen consisting of 80 mg/kg of BU injected twice daily over four days (total 8 injections of 10 mg/kg) followed by two daily injection of 100 mg/kg of CY for a total of 200 mg/kg [94].…”
Section: Chemotherapy-based Conditioningmentioning
confidence: 99%
See 1 more Smart Citation